2009
DOI: 10.1142/s0217984909020540
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY ON STRAIN AFFECTING ELECTRONIC STRUCTURE OF WURTZITEZnOBY FIRST PRINCIPLES

Abstract: Density of states and band structure of wurtzite ZnO are calculated by the CASTEP program based on density functional theory and plane-wave pseudopotential method. The calculations are carried out in axial and unaxial strains, respectively. The results of density of states in different strains show that the bottom of the conduction band is always dominated by Zn 4s, and the top of valence band is always dominated by O 2p. The variation of the band gap calculated from band structure is also discussed. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This a-axis compressive strain may also be one of the reasons resulting in the UV enhancement, which is consistent with the work of Yang et al [24]. Besides, Li et al reported based on their calculation that the decrease of bandgap of ZnO along uniaxial a-axis compressive strain is attributed to the variation of hybridization of atomic orbits [25]. Thus this compressive strain observed after low energy irradiation is likely one of reasons that causes the red shift of the UV emission, as shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…This a-axis compressive strain may also be one of the reasons resulting in the UV enhancement, which is consistent with the work of Yang et al [24]. Besides, Li et al reported based on their calculation that the decrease of bandgap of ZnO along uniaxial a-axis compressive strain is attributed to the variation of hybridization of atomic orbits [25]. Thus this compressive strain observed after low energy irradiation is likely one of reasons that causes the red shift of the UV emission, as shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…Shi et al have reported that, in an under-strain ZnO supercell, the bottom of the conduction band is dominated by the Zn 4s level and the O 2p level is determinative for the top of the valence band. Based on the density functional theory and the plane-wave pseudopotential method, they found that when c-axial strain varies from tensile to compressive, the O 2p level shifts to a lower energy while Zn 4s shifts oppositely; therefore, the band gap of ZnO increases linearly with decreasing c [25]. Our experimental result on individual ZnO nanowires provides strong evidence that the strain can bring about the linear variation in the band gap of ZnO, which is well consistent with the theoretical prediction.…”
Section: Resultsmentioning
confidence: 99%
“…The peak positions of the four emission bands did not exhibit any appreciable shift under straining (Figure c), but they did have obvious blue shift as the applied bias voltage was increased (see Section B in Supporting Information). It is known that the bandgap of ZnO decreases under compressive a- axis strain, while the bandgap of GaN also decreases under compressive c -axis strain. , In this case, the peak position should have a red shift under compressive strain. On the other hand, the emission centers of the n-ZnO/p-GaN LED have blue shift with the increase of injection current due to the band renormalization, band filling at high current and/or the increased kinetic energies of electrons and holes .…”
mentioning
confidence: 99%